The ten principles behind great customer experiences - Watkinson, Matt (Pearson Education, 2013)
Create a great customer experience whoever you are. Customers are powerful. They have a loud voice, a wealth of choice and their expectations are higher than ever. . This book covers ten principles you can use to make real world improvements to your customers' experiences, whatever your business does and whoever you are. . For managers, leaders and those starting a new business, the book shows that making improvements customers will appreciate doesn't need to be complicated or cost a fortune. . . Written for results. Practical advice that's easy to implement. Start making improvements fast. . Everything you need. Get started immediately using the companion worksheets. . No jargon. Effortless to read. No previous knowledge required. . Inspiring examples. Key ideas are brought to life by great case studies. . Universally applicable. The principles work for any product or service, however large the business. . Concise and skimmable. Read a chapter a day on your commute. Get what you need, whatever your time limits. Matt Watkinson is a designer and consultant who helps businesses get their customer experience right. Publisher's note.